AJARAN MORAL BERUMAH TANGGA DALAM SERAT DARMAWASITA KARYA K.G.P.A.A. MANGKUNAGORO IV - Djoko Pitoyo (Jurnal Filsafat "WISDOM", 2009)
AbstractSerat Darmawasita was written by K.G.P.A.A. Mangkunagoro IV in 1879 A.D. The overall lyrics of the Serat imply some advices or moral teachings on household affairs for spouses in order to maintain the solidity, the harmony and continuance of their marriage life. Relationship between husband and wife is maintained carefully based on their understanding on their own rights and duties. All those positions, attributes, and roles between husband and wife, of course, correspond to the cultural values, spirits and atmosphere of Javanese noble family at that time.Several moral teachings on household affairs might be appropriated as a reference or an inspiration for us, such ascommunication between husband and wife would be better performed in serenity so that there will be a harmony within thehousehold. The courtesy should be given a priority for the sake of solidity, harmony and continuance of the husband-wife relationship within the family. Accordingly, life would be not only good, but also proper and beautiful.Keyword: morality, household, husband, wife, rights, responsibility.